Pengembangan Program Simulasi Planetary Gear Set Dengan Kombinasi Gear Rasio - Asrul Sudiar (POLITEKNIK NEGERI BENGKALIS, 2019)
Various components in a powertrain system can consist of a series of several components that aim to continue the engine rotation from the flywheel to the torque conventer then proceed to the transmission and then to the bevel gear to the final drive, have a variety of different types of technology and of course have advantages and each other's shortcomings. Of the various components, there are several types of components that use a device called the Planetary Gear Set, including the powershift transmission, torque divider and final drive. With the Planetary Gear Set, the rotation of the engine will be able to be doubled in torque as needed when the unit is running and with the combination produced from the Planetary Gear Set it will be possible to create various speed combinations both in the direction of the engine speed and vice versa.This research aims to create and design an application (Engineering Software) to study the workings of the Planetary Gear Set which consists of 3 basic components, namely: Ring Gear, Sun Gear and Planetary Carrier with various interactive gear ratio combinations, which will facilitate students in The Department of Mechanical Engineering in general and the Heavy Equipment Study Program especially in learning the workings of the Planetary Gear Set, so that it is expected to be a tool in the learning and teaching process.Keyword: Planetary Gear Set, Engineering Software.